Glioma in Schizophrenia: Is the Risk Higher or Lower? - Gao, Xingchun; Mi, Yajing; Guo, Na; Xu, Hao; Jiang, Pengtao; Zhang, Ruisan; Xu, Lixian; Gou, Xingchun (Frontiers in Cellular Neuroscience, 2018)
Whether persons with schizophrenia have a higher or lower risk for cancer has been discussed for a long time. Due to the complex mechanisms and characteristics of different types of cancer, it is difficult to evaluate the exact relationship between cancers and schizophrenia without considering the type of tumour. Schizophrenia, a disabling mental illness that is now recognized as a neurodevelopmental disorder, is more correlated with brain tumours, such as glioma, than other types of tumours. Thus, we mainly focused on the relationship between schizophrenia and glioma morbidity. Glioma tumourigenesis and schizophrenia may share similar mechanisms; gene/pathway disruption would affect neurodevelopment and reduce the risk of glioma. The molecular defects of DISC1, P53, BDNF and CXCR4 involved in schizophrenia pathogenesis might play opposite roles in glioma development. Many miRNAs such as miR-183, miR-9, miR-137 and miR-126 expression change may be involved in the cross talk between glioma prevalence and schizophrenia. Finally, antipsychotic drugs may have antitumour effects. All these factors show that persons with schizophrenia have a decreased risk for glioma; therefore, epidemiological investigation and studies comparing genetic and epigenetic aberrations involved in both of these complex diseases should be performed. These studies can provide more insightful knowledge about glioma and schizophrenia pathophysiology and help to determine the target/strategies for the prevention and treatment of the two diseases.